PERANCANGAN WEB E-COMMERCE UNTUK PENJUALAN SEPATU DENGAN PENDEKATAN MODEL CLASSIC LIFE CYCLE - Ika Yuniva; Dany Hestiyanto (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2018)
A Website is not only used as a medium of information, but also used as a media campaign both in the field of business, service and so forth. One of them a Home Industry Shoes require promotion media through the website to expand the marketing so as to support sales revenue and provide convenience for anyone who needs Shoes made Home Industry. Rizky Shoes is a Home Industry engaged in the manufacture and sale of Handmade Shoes. Currently the ordering and sales process is still conventional, customers can come directly to the Home Industry Rizky Shoes and recording transactions are still manual using paper. The purpose of this study is to produce an e-commerce website as a media campaign and marketing and help Home Industry Rizky Shoes in increasing sales. This research uses case study with observation method and literature study in collecting data. System requirements on this e-commerce web Admin can make the process of goods input, display data or data deletion process, change the status of purchases. While users can make reservations, view products, register as a member, and make payment confirmation. For software development method using classic life cycle approach. Data model described by ERD (Entity Relationship Diagram) and LRS (Logical Record Structure) While the database using MySQL and programming languages using PHP.